The Effect of Job Promotion and Competence on Employee Performance through Career Development - Abdul Holiq Firdaus; Muhammad Firdaus; Tamriatin Hidayah (Innovation Business Management and Accounting Journal, 2024)
The purpose of this study was to analyze and determine the effect of job promotion and employee competence on the performance of employees of the Bondowoso Regency Education Office through career development as an intervening variable. This research method is explanatory research with a quantitative approach. Data collection techniques consist of observation, questionnaires and literature studies. The population and sample of the study were 100 employees of the Bondowoso Regency Education Office. The data analysis technique was path analysis operated with the SPSS (Statistical Product and Service Solutions) version 24 application. Based on the results of the data analysis, it shows that job promotion and competence have a significant effect on the career development of employees of the Bondowoso Regency Education Office. Furthermore, job promotion, competence and career development have a significant effect on the performance of employees of the Bondowoso Regency Education Office. Finally, career development in this study was able to provide a mediating effect between the relationship between job promotion and competence on the performance of employees of the Bondowoso Regency Education Office. The implication of the study is that the Bondowoso Regency Education Office needs to evaluate the suitability of employee competence with the positions held in certain positions. This provides wider opportunities for career development of employees who have good competence and work skills. Apart from that, it is necessary to consider length of service and work performance to give promotions to employees.